Developing information literacy skills of the 6th grade students using the Big 6 model - Baji, Fatima; Bigdeli, Zahed; Parsa, Abdullah; Haeusler, Carole (Malaysian Journal of Library and Information Science, 2018)
The Big6 model is a systematic approach to information problem-solving that relies upon critical thinking skills. It is the most used model for information literacy instruction in schools worldwide. Since there is a lack of information literacy skills instruction in the educational system of Iran, especially in primary schools, this research evaluates an information literacy intervention in the Iranian 6thgrade science classroom. The study employs a mixed-method explanatory design using a true experimental method with pre-test and post-tests. The qualitative phase investigated the experiences and perceptions of the experimental group. Results show that integrating the Big6 model into the primary science curriculum helps the students to improve their information literacy skills as well as gain a deeper understanding of the research process. Overall, the research contributes evidence to show the effectiveness of a collaborative teaching approach in information literacy instruction. This approach promotes positive attitudes among students towards the school library and the school librarian’s role in the educational process.